Natural heritage of environmentally sensitive areas in Kuala Selangor district, Malaysia - Asmawi, M. Zainora; Paiman, Tuminah (International Proceedings of Chemical, Biological and Environmental Engineering (IPCBEE), 2015)
This paper addresses the issue of the conserving the natural heritage of environmentally sensitive areas in Kuala Selangor District, Malaysia. Being as environmental goods, the existence of these natural heritage elements is all important as overall it enhances the quality of life. Simultaneously, it is greatly marked that presently there is an increasing tendency in the development which may hamper these sensitive areas. Thus, this research was embarked to analyses the importance of areas of natural heritage found in Kuala Selangor. The research mainly employed the collection of secondary information in terms of textual and statistical information in the form of GIS format to assemble info for analysis purpose. The results indicate that the natural heritage of environmentally sensitive areas comprises of Kuala Selangor Nature Park, Kampung Kuantan, Kampung Bukit Belimbing and Permanent Forest Reserves. These fields hold the prominent values of historical archaeology and biodiversity which should be protected for future generations. As a conclusion, it is clearly evident that environmental goods, letting in natural heritage have invaluable assets that hold its own contribution to raising the overall environmental quality.